Ambient Air Blade‐Coating Fabrication of Stable Triple‐Cation Perovskite Solar Modules by Green Solvent Quenching. Issue 8 (16th May 2021) - Vesce, Luigi; Stefanelli, Maurizio; Herterich, Jan Philipp; Castriotta, Luigi Angelo; Kohlstädt, Markus; Würfel, Uli; Di Carlo, Aldo
Abstract : Although halide perovskite solar cell (PSC) technology reaches, in few years, efficiencies greater than 25%, the cost‐ceffective perspective is achievable only if scalable processes in real manufacturing conditions (i.e., pilot line and/or plant factory) are designed and optimized for the full device stack. Herein, a full semiautomatic scalable process based on the blade‐coating technique is demonstrated to fabricate perovskite solar modules in ambient conditions. An efficient and stable triple‐cation cesium methylammonium formamidinium (CsMAFA) perovskite is deposited in ambient air with a two‐step process assisted by air and green anti‐solvent quenching. The developed industry compatible coating process enables the fabrication of several highly reproducible small‐area cells on module size substrate with an efficiency exceeding 17% and with high reproducibility. Corresponding reproducible modules (less than 2% variability) with a 90% geometrical fill factor achieve an efficiency larger than 16% and T 80 = 750 h in light‐soaking condition at maximum power point and room temperature/ambient after encapsulation. Film deposition properties are assessed by different characterization techniques, namely, scanning electron microscopy, profilometry, UV–vis and photoluminescence (PL) spectroscopy, and PL and electroluminescence imaging. The techniques confirm less defects and local coating variations of the ambient air/bladed devices with respect to the nitrogen air/spinned devices. Abstract : A semiautomatic and scalable solvent quenching/double‐step method is demonstrated to deposit the triple cation perovskite in ambient air on module size substrate (first time in literature). The champion efficiency is 16.1% with high reproducibility and layers homogeneity. The module has a T80 of 750‐h in light‐soaking condition at maximum power point (MPP), room temperature, and ambient atmosphere.